Effect of Unsaturated to Saturated Fatty Acids Ratio of Supplemental Fat in the Diet with or without L-Carnitine on Performance of Broiler Chicken - Swarna, Ch. Leela; Rao, S.V. Rama; Srinivas, Gurram; Reddy, V. Ravinder (Indian Journal of Animal Nutrition, 2018)
The present trial was conducted to study the effect of ratio of unsaturated to saturated fatty acids with or without L-carnitine supplementation on the performance male broiler chicks. A total of 320 day old male broiler chicks were randomly divided into 8 treatments with eight replicate and five birds each. T1, T2, T3 and T4 diets were formulated to contain ratio of UFA: SFA fatty acids as 60: 40, 65: 35, 70: 30 and 75: 25, respectively. Diets T5, T6, T7 and T8 were formulated to contain same ratio of fatty acids to that of T1 to T4 but with supplementation of L-carnitine at 100 mg/kg diet level. Before the feed formulation, the lipid profile of the tallowand crude soybean oil were analyzed. The unsaturated fatty acids (UFA) : saturated fatty acids (SFA) ratio were found to be 5.37 and 0.77, respectively for crude soybean oil and tallow. The results indicated that 70: 30 ratio without L-carnitine had significantly (P